Targeted inhibition of endothelial calpain delays wound healing by reducing inflammation and angiogenesis - Yi, Chenlong (Cell Death Dis, 2020)
Wound healing is a multistep phenomenon that relies on complex interactions between various cell types. Calpains are a well-known family of calcium-dependent cysteine proteases that regulate several processes, including cellular adhesion, proliferation, and migration, as well as inflammation and angiogenesis. CAPNS1, the common regulatory subunit of Calpain-1 and 2, is indispensable for catalytic subunit stabilization and activity. Calpain inhibition has been shown to reduce organ damage in various disease models. Here, we report that endothelial calpain-1/2 is crucially involved in skin wound healing. Using a mouse genetic model where Capns1 is deleted only in endothelial cells, we showed that calpain-1/2 disruption is associated with reduced injury-activated inflammation, reduced CD31(+) blood vessel density, and delayed wound healing. Moreover, in cultured HUVECs, inhibition of calpain reduced TNF-α-induced proliferation, migration, and tube formation. Deletion of Capns1 was associated with elevated levels of IκB and downregulation of β-catenin expression in endothelial cells. These observations delineate a novel mechanistic role for calpain in the crosstalk between inflammation and angiogenesis during skin repair.